The mating system of the true fruit fly Bactrocera tryoni and its sister species, Bactrocera neohumeralis. (25th May 2016) - Ekanayake, Wasala M. T. D.; Jayasundara, Mudalige S. H.; Peek, Thelma; Clarke, Anthony R.; Schutze, Mark K.
Abstract: The frugivorous "true" fruit fly, Bactrocera tryoni (Queensland fruit fly), is presumed to have a nonresourced‐based lek mating system. This is largely untested, and contrary data exists to suggest Bactrocera tryoni may have a resource‐based mating system focused on fruiting host plants. We tested the mating system of Bactrocera tryoni, and its close sibling Bactrocera neohumeralis, in large field cages using laboratory reared flies. We used observational experiments that allowed us to determine if: (i) mating pairs were aggregated or nonaggregated; (ii) mating system was resource or nonresource based; (iii) flies utilized possible landmarks (tall trees over short) as mate‐rendezvous sites; and (iv) males called females from male‐dominated leks. We recorded nearly 250 Bactrocera tryoni mating pairs across all experiments, revealing that: (i) mating pairs were aggregated; (ii) mating nearly always occurred in tall trees over short; (iii) mating was nonresource based; and (iv) that males and females arrived at the mate‐rendezvous site together with no evidence that males preceded females. Bactrocera neohumeralis copulations were much more infrequent (only 30 mating pairs in total), but for those pairs there was a similar preference for tall trees and no evidence of a resource‐based mating system. Some aspects of Bactrocera tryoni mating behavior align with theoretical expectations of a lekking system, but others do not. Until evidence for unequivocal female choice can be provided (as predicted under a true lek), the mating system of Bactrocera tryoni is best described as a nonresource based, aggregation system for which we also have evidence that land‐marking may be involved.